Analisis Aksesibilitas dan Tingkat Penggunaan Ruang Terbuka Hijau Publik Kota Kendari - Muhammad, Alfayed Rahmat; Sulistyantara, Bambang; Thajono, Budi (Jurnal Lanskap Indonesia, 2025)
Kendari City adopts the green city concept; however, urban development has led to population growth and residential expansion, resulting in the degradation of Green Space quantity. In 2024, the population reached 98% of the previous year total, while residential areas expanded by 122.44 ha, reducing the accessibility of public green space. This study aims to evaluate public Green Space spatially through accessibility analysis and user perception. The research employs a qualitative method supported by quantitative data. Data collection techniques include interviews, questionnaires, surveys, observations, and documentation. Respondents were selected using stratified random sampling, targeting individuals aged 18–55 years from each district. Questionnaire data were analyzed using Pearson Chi-square (X²) correlation, while spatial analysis applied the non-parametric bivariate t-test to examine variable relationships. The findings indicate that key factors influencing public green space usage include landscape planning that considers greenery, economic value, culture, aesthetics, safety and health. Connectivity with public facilities and residential areas should be improved through adequate transportation infrastructure. In addition, traffic aspects must be addressed to accommodate working-age groups and recreational purposes. The final evaluation synthesizes spatial and perceptual analyses into landscape planning recommendations to enhance the quality and accessibility of public green space in Kendari City.